2010
DOI: 10.1007/s10236-010-0333-z
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of wave dissipation at the Hendijan mud coast, the Persian Gulf

Abstract: Effects of non-rigid muddy bed on the wave climate at the Hendijan coast along the northwestern part of the Persian Gulf have been examined through field measurements and numerical wave transformation modeling. The field survey included measurements of wave characteristics at an offshore and a nearshore station, and mud sampling to obtain the thickness of the fluid mud layer and its rheological properties. Comparisons of wave spectra at the two stations show energy dissipation along the wave trajectory with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…First, the damping expression (34) assumes a 1/ dependence between the elastic and viscous responses of the sediment, and combines both dissipation mechanisms into one single term. In contrast, experimental studies [39,[45][46][47][48][49] that have reported both the shear and the viscous properties (flow curves) of sediments do not suggest a straightforward 1/ dependence between the two. The elastic and the viscous responses may vary individually, depending on the strain amplitude and/or frequency ranges (in for example, shear viscosity [58,59] and elastic modulus [61]).…”
Section: Linear Expressions Of Anderson and Hampton (1980)mentioning
confidence: 86%
See 2 more Smart Citations
“…First, the damping expression (34) assumes a 1/ dependence between the elastic and viscous responses of the sediment, and combines both dissipation mechanisms into one single term. In contrast, experimental studies [39,[45][46][47][48][49] that have reported both the shear and the viscous properties (flow curves) of sediments do not suggest a straightforward 1/ dependence between the two. The elastic and the viscous responses may vary individually, depending on the strain amplitude and/or frequency ranges (in for example, shear viscosity [58,59] and elastic modulus [61]).…”
Section: Linear Expressions Of Anderson and Hampton (1980)mentioning
confidence: 86%
“…The elastic and the viscous responses may vary individually, depending on the strain amplitude and/or frequency ranges (in for example, shear viscosity [58,59] and elastic modulus [61]). These may furthermore depend on the salinity, the mineralogical composition and the concentration [46,48]. Second, there exists a discrepancy because of the use of Re( * ) in the resonance frequency expression (35) and Im( * ) in the damping coefficient (34).…”
Section: Linear Expressions Of Anderson and Hampton (1980)mentioning
confidence: 99%
See 1 more Smart Citation
“…The north-western part of the Persian Gulf is covered with mud, originated mainly from the catchment area of Arvand River (Haghshenas and Soltanpour, 2010). Mud deposits up to 20 meters thickness is observed at the very shallow coast of Hendijan Fishery Port, located at the north-western shoreline of the Deylam Bay; while very fine sand with oolitic origin is dominant at Deylam Port in the south-eastern corner of the bay.…”
Section: Coastal Engineering 2014mentioning
confidence: 99%
“…A set of field measurements was performed at the field site from 20th of February to 28th of March, 2007 (Haghshenas andSoltanpour, 2010). Directional wave spectra and vertical current profiles were simultaneously recorded at two nearshore (2.5 m deep) and offshore (10 m deep) stations.…”
Section: Field Measurementsmentioning
confidence: 99%